Computational materials design of LiZnAs-, LiZnP-, and LiZnN-based n-type magnetic semiconductors. (14th April 2015) - Vu, Nguyen Dang; Fukushima, Tetsuya; Sato, Kazunori; Katayama-Yoshida, Hiroshi
Abstract: The computational materials design of n-type filled tetrahedral compound magnetic semiconductors is proposed on the basis of first-principles calculations within the density functional theory. Using the Korringa–Kohn–Rostoker coherent potential approximation, the electronic structures of electron-doped Li(Zn, Mn)As, Li(Zn, Mn)P, and Li(Zn, Mn)N are calculated. By estimating free energy, the phase diagrams of these systems are predicted. It is shown that these systems are phase-separated and favor spinodal decomposition when the electrons are not doped. By introducing Li interstitials as donor impurities, spinodal decomposition is strongly suppressed and Mn can be doped at a high concentration. Moreover, ferromagnetic interactions between Mn atoms are induced by electron doping. Thus, we can expect electron-mediated ferromagnetism in these systems with a reasonable Curie temperature.